ANALISIS PENGARUH TRANSPARANSI DAN AKUNTABILITAS TERHADAP PENGELOLAAN KEUANGAN DAERAH KABUPATEN ROKAN HULU - Sarmini; Andi Afrizal (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2019)
This study aims to determine the effect of transparency and accountability on local financial management in Rokan Hulu Regency. The population in this study are all officials who carry out regional financial management. The study sample used a proportional random sampling technique with a total of 87 people. Data collection methods using observation, questionnaires, documentation and interviews. Data analysis using multiple linear regression with the SPSS program. The results of multiple linear regression analysis obtained regression equation Y = 7.280 + 1.017X1 + 1.426X2. Partially, transparency count 4,239 and accountability 7,629 were obtained. Simultaneously, an F-count of 114,933 was obtained. The results showed that 73.2% of regional financial management was influenced by transparency and accountability, while the remaining 26.8% was influenced by other variables not examined in this study. The conclusion of this study. Both the partial test (t test) and the simultaneous test (F test) all independent variables consisting of transparency and accountability simultaneously affect the management of regional finances